Lecturers’ perceptions of flipped learning in higher education: A case study on flipped classroom implementation in Singapore Polytechnic (Journal of Applied Learning and Teaching, 2022)
Higher education institutions have adopted flipped learning in recent years, and it is worthwhile to examine how the users have perceived such a change. While many research studies focused on students as participants, this study examines the lecturers' perception of flipped learning. Findings in the study showed that both lecturers’ perceived student behaviour and instructional consideration had a significant and positive effect on student learning. The study also attempted to examine whether lecturers’ experience in flipped learning would moderate instructional consideration and student learning. Results showed that lecturers’ experience in flipped learning had no influence on instructional consideration and student learning.